Preventing Catheter-Associated Urinary Tract Infection: A Multipronged Collaborative Approach. Issue 1 (January 2020) - Mundle, William; Howell-Belle, Carnett; Jeffs, Lianne
Abstract : Background: Research has shown that catheter-associated urinary tract infections (CAUTIs) are highly preventable and have significant impact on patient morbidity and mortality as well as financial consequences for the health care system. Local: CAUTI rates were documented to be higher in the general internal medicine units when compared with the overall hospital rates. Methods: A comparative analysis was undertaken. Intervention: An interprofessional working group developed and implemented a quality improvement initiative bundled approach to reducing CAUTIs. Results: There was a 79% reduction in average CAUTI rates following the bundle implementation along with reduced variability in rates. Conclusions: Implementation of a standardized bundle of practices aimed at reducing CAUTIs resulted in decreased CAUTI rates. Organizations can use the design and implementation approach to reduce and minimize CAUTI rates, which can positively impact cost, care experience, and outcomes. Abstract : Supplemental Digital Content is Available in the Text.